Unveiling diversity in inhabited and uninhabited reefs of the Lakshadweep archipelago, India using eDNA - Ammanabrolu, Bharath Subramanyam; Dineshram, Ramadoss (Frontiers in Marine Science, 2025)
Coral reefs are important ecosystems that host a variety of life and provide essential services to ecosystems and people. But they are increasingly at risk due to human activities and climate change. In India, Lakshadweep coral reefs support a significant proportion of the local population’s livelihood, being a promising area with a wide range of fish, mollusks, crustaceans and seaweeds. And, in addition to the human activities, the earlier three El Nino events impacted Lakhadweep coral reefs with significant coral mortality. Therefore, it is crucial to continuously and rapidly assess their biodiversity to monitor the health of the reef. Due to its advantages over traditional methods, environmental DNA (eDNA) metabarcoding is an efficient tool for continuous monitoring and is non-invasive. However, there have been limited eDNA studies, and none have been conducted on the Lakshadweep islands in India considering human inhabitation. The present study conducted an eDNA-based biodiversity assessment focusing on the metazoan community using a COI gene fragment amplified with Mico1intF and jgHCO2198 primers targeting approximately 350bp. The study recovered genetic information of key species, 4 Families of Scleractinia, Poritidae, Pocilloporidae, Euphyllidae, and Merulinidae, 9 Species of Echinoderms and 19 species of fish communities. In addition to this, 12 different taxa of Arthropoda, 6 Mollusks and 7 Porifera. In total, 25 different taxa were observed in the Algal community, including micro- and Macroalgal assemblages. A total of 15 phyla were recorded from both human-inhabited and uninhabited Reefs. Fish communities were more abundant in uninhabited reefs, and the number of detected taxa was also higher in uninhabited reef samples. Previous biodiversity assessments in the Lakshadweep archipelago relied on occasional underwater surveys, lacking continuous monitoring. Our study, employing eDNA monitoring, provides a baseline for continuous and rapid biodiversity study in monitoring the status using genetic information with the perspective of human inhabitation in the Lakshadweep coral reefs.